THE ANALYSIS OF THE THEORY OF PLANNED BEHAVIOR ON THE INTEREST OF SURABAYA'S CITIZENS FOR SHARIA OWNERSHIP CREDIT IN DE RAYYAN DEVELOPER PROPERTY - Arif Dwi Harnoko; Sri Herianingrum (Universitas Airlangga, 2020)
This study is composed to prove whether the Theory of Planned Behavior variables, namely attitudes, subjective norms, and behavioral control perceived by the citizens of Surabaya have a significant effect on their intention to Sharia House Ownership Loans (De Rayyan Developer Property). This is a quantitative study by using multiple regression analysis techniques. Criteria of respondents in this study were residents of Surabaya according to the criteria that has been established by the researcher. The total sample obtained was 94 people by using a simple random sampling technique. The findings of this study indicated that the exogenous variables in the Theory of Planned Behavior are subjective norms, and perceived behavioral control has a significant effect on Surabaya residents' intentions for Sharia Home Ownership Loans. On the contrary, the attiude variable does not significantly influence the intention of residents of Surabaya for shariah home ownership credit. The suggestion of this research is to add new exogenous variables that have the possibility of having significant effects such as the level of religiosity and trust in Sharia Property Developer.Keywords: Sharia House Ownership Credit, Intention, Theory of Planned Behavior, Surabaya Citizen, De Rayyan Property Developer